Analisa Penyelenggaraan Asuransi Kendaraan Bermotor - pardomuan, andreas rio (Peneliti.net, 2024)
In the consumer financing agreement for motorized vehicles, there are 3 parties involved, namely: (1) the creditor, which is a business entity that finances installments for consumer needs, be it cars or motorcycles, by means of periodic payments or installments; (2) debtors, who are consumers who use the services of creditors who receive financing facilities to purchase motorized vehicles; (3) dealers, which are companies that supply consumer goods in the context of consumer financing. Insurance is very closely related to each other with risk and in risk management, insurance is precisely the way that is considered appropriate for dealing with a risk. The limitations of an insurance agreement are discussed in article 246 of the Criminal Code as follows: Insurance or coverage is an agreement, in which an insurer binds himself to an insured, by asking for a premium, to provide compensation to him due to a loss, damage, loss of expected profits, which may be suffered due to an unspecified event.